Kajian Materi Pendidikan Agama Islam dengan Pendekatan Antropologi - Ishak Ishak; Tobroni Tobroni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the study of Islamic religious education materials with an anthropological approach. The purpose of this study is to study religion from an anthropological perspective, study Islamic religious education from the perspective of local and global cultural values ​​and study the design of Islamic religious education materials for the advancement of civilization. The research method used is qualitative research with a social, cultural and religious phenomenon approach. Data collection carried out is observation, interviews, documentation, namely collecting written data, such as Islamic religious education textbooks, educational policies. Data analysis used is thematic analysis, hermeneutics, triangulation and interdisciplinary approaches. The results of the study show that the perspective of religious anthropology emphasizes understanding and appreciation of the diversity of religious practices in societies around the world. Islamic religious education must be holistic and inclusive by considering local and global cultural values. A holistic and interdisciplinary approach is expected in the design of religious education materials to integrate religious values ​​with the needs of the times, so that a generation that understands religion deeply and is able to face the challenges of society.